Analysis of Italian isolates of Pantoea stewartii subsp. stewartii and development of a real-time PCR-based diagnostic method - Scala, Valeria; Faino, Luigi; Costantini, Francesca; Crosara, Valeria; Albanese, Alessio; Pucci, Nicoletta; Reverberi, Massimo; Loreti, Stefania (Frontiers in Microbiology, 2023)
Pantoea stewartii subsp. stewartii (Pss) causes Stewart’s vascular wilt of maize and it is responsible for serious crop losses. Pss is indigenous of North America and spreads with maize seeds. The presence of Pss has been notified in Italy since 2015. The risk assessment of the entry of Pss in the EU from the USA, through seed trade is in the order of magnitude of hundred introductions per year. Several molecular or serological tests were developed for the detection of Pss and used as official analysis for the certification of commercial seeds. However, some of these tests lack adequate specificity, not allowing to correctly discriminate Pss from P. stewartii subsp. indologenes (Psi). Psi is occasionally present in maize seed and is avirulent for maize. In this study, several Italian isolates of Pss recovered in 2015 and 2018 have been characterized by molecular, biochemical and pathogenicity tests; moreover, their genomes have been assembled through MinION and Illumina – sequencing procedures. Genomic analysis reveals multiple introgression events. Exploiting these results, a new primer combination has been defined and verified by real-time PCR, allowing the development of a specific molecular test able to detect the presence of Pss down to the concentration of 103 CFU/mL in spiked samples of maize seed extracts. Due to the high analytical sensitivity and specificity achieved with this test, the detection of Pss has been improved disentangling the inconclusive results in Pss maize seed diagnosis, overcoming its misidentification in place of Psi. Altogether, this test addresses the critical issue associated with maize seeds imported from regions where Stewart's disease is endemic.